Microstructural Evolution and Strain-Hardening Behavior in Hadfield Steel Railway Crossings - Gustavo Tressia; Tiago Tepedino; Mohammad Masoumi; Juan Ignacio Pereira (Tribology in Industry)
This work examines defect (spalling) in a railway crossing (frog) removed from a heavy-haul railway after 120 Milling Gross Tons (MGT). The frog was manufactured using standard Hadfield steel. The steel microstructure evolution was analyzed to understand crack initiation and propagation during service. Scanning electron microscopy (SEM), X-ray diffraction, and electron backscattered diffraction (EBSD) methods were employed to characterize microstructural changes near the crack region. Furthermore, local mechanical properties were assessed using nanoindentation tests and sub size tensile tests. SEM analysis revealed that twinning is the primary work-hardening mechanism, with the absence of phase transformation confirmed by XRD. The interaction of dislocation walls and twin structures generated by twinning-induced plasticity increased the local hardness of Hadfield steel up to 8.5 GPa, substantially reducing ductility. Peak broadening of austenite phases was observed, indicating significant crystal defect densities under cyclic loading. Microstructural analysis in defect regions showed that these defects originated from the nucleation and propagation of cracks in grain boundaries with carbides. This investigation demonstrates that the reduced service life of the railway frog is associated with manufacturing process defects and contributes to understanding material deformation mechanisms, aiding in the development of more resilient steels for such applications.